Strategy to Conserve Maximum Biodiversity of Limestone Flora in Peninsular Malaysia - Rahman, Rafidah Abdul; Kiew, Ruth (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2018)
The need to exploit limestone products for national development impacts on the conservation of rare and endangered limestone species. To minimise this impact it is necessary to identify which of the 570 limestone outcrops have high conservation importance and whether they have narrowly endemic and/or endangered limestone species. In the absence of detailed checklists for each outcrop, the Gesneriaceae is selected as being biodiverse on limestone, being well collected and outstanding in the number of endemic species and/or species restricted to limestone for mapping. Of the 210 species in the 25 genera of Gesneriaceae in Peninsular Malaysia, 42 species belonging to the genera Damrongia Kerr ex Craib, Emarhendia Kiew, A.Weber & B.L.Burtt, Epithema Blume, Microchirita (C.B.Clarke) Yin Z.Wang, Monophyllaea R.Br., Ornithoboea Parish ex C.B.Clarke, Paraboea (C.B.Clarke) Ridl., Senyumia Kiew, A.Weber & B.L.Burtt and Spelaeanthus Kiew, A.Weber & B.L.Burtt grow on limestone hills. Of these 42 species, 28 are endemic and 16 are restricted to a single or adjacent hills. Mapping their distribution shows that in common with other families there are three distinct phytogeographical provinces (the Northern Province, Perak Province and the Asian Intrusion) but that the narrowly endemic species do not cluster on particular hills, nor does their distribution coincide with those of other narrowly endemic species in other families. This illustrates that a network comprising a large number of hills, not only those within the three provinces but also all those harbouring narrowly endemic species that are at risk of extinction if not conserved, is necessary to maximise conservation of the biodiversity of the limestone flora.